Annual report 2017 : agriculture: opportunity for development in the Americas: Dominica - Instituto Interamericano de Cooperación para la Agricultura (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2018)
This annual report focuses on activities relating to productivity and growth in agro-enterprises, resilience, strengthening producer organizations, and agricultural health and food safety, in collaboration with local and international organizations. The Institute anticipates the continued close, partnership and collaboration with the Ministry of Agriculture and Fisheries, the Organization of Eastern Caribbean States, the private sector, farmer organizations, international organizations, and women and youth organizations in executing the Institute’s pro-gramme for 2018.